2001
DOI: 10.1111/j.1572-0241.2001.03935.x
|View full text |Cite
|
Sign up to set email alerts
|

Provocation of transient lower esophageal sphincter relaxations by gastric distension with air

Abstract: Short-lasting gastric air distension 1) provokes TLESRs but does not differentiate GERD patients from controls, 2) reveals impaired belching capacity in patients after complete fundoplication, and 3) shows that common cavities do not exclusively occur during TLESRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 19 publications
5
40
0
5
Order By: Relevance
“…Risk factors for gastro-oesophageal reflux include smoking, obesity, alcohol consumption [7], physical inactivity and dietary factors [8]. Previous studies also suggested that gastric distention by gas or liquid boluses could cause transient relaxation of the lower oesophageal sphincter which is likely to increase frequency of reflux episodes [9,10]. Although, reflux of liquid stomach contents is most likely to result in measurable reflux, previous hypothesis has also suggested that the retrograde movement of gas boluses could also coat the mucosal lining of the aerodigestive tract with small volumes of aerosolized gastric juice [10].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for gastro-oesophageal reflux include smoking, obesity, alcohol consumption [7], physical inactivity and dietary factors [8]. Previous studies also suggested that gastric distention by gas or liquid boluses could cause transient relaxation of the lower oesophageal sphincter which is likely to increase frequency of reflux episodes [9,10]. Although, reflux of liquid stomach contents is most likely to result in measurable reflux, previous hypothesis has also suggested that the retrograde movement of gas boluses could also coat the mucosal lining of the aerodigestive tract with small volumes of aerosolized gastric juice [10].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown delayed gastric emptying in patients with GERD [80,81,82,83,84,85]. In theory, delayed gastric emptying could lead to accumulation of a larger intragastric volume of solids and liquids leading to reflux [86] or the resultant gastric distension may provoke more TLESRs [36, 87, 88], possibly through activation of gastric mechanoreceptors [37,38,39, 89, 90]. On the other hand, several studies have failed to show a correlation between delayed gastric emptying and increased gastroesophageal reflux.…”
Section: Gastric Dysmotilitymentioning
confidence: 99%
“…Our group previously reported more GER events during wake-state 26 and attributed it to a higher frequency of transient lower esophageal sphincter relaxation and postprandial gastric distention 27 during wake-state. However during our analysis of pH studies, meal periods were appropriately excluded.…”
Section: Discussionmentioning
confidence: 83%